2017
DOI: 10.3389/fimmu.2017.01007
|View full text |Cite
|
Sign up to set email alerts
|

The Activity of the Neutral Sphingomyelinase Is Important in T Cell Recruitment and Directional Migration

Abstract: Breakdown of sphingomyelin as catalyzed by the activity of sphingomyelinases profoundly affects biophysical properties of cellular membranes which is particularly important with regard to compartmentalization of surface receptors and their signaling relay. As it is activated both upon TCR ligation and co-stimulation in a spatiotemporally controlled manner, the neutral sphingomyelinase (NSM) has proven to be important in T cell activation, where it appears to play a particularly important role in cytoskeletal r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 57 publications
(56 reference statements)
2
44
0
Order By: Relevance
“…The nocodazole treatment did not affect total ATP levels in CTRL and NSM KD cells ( Figure 1C ). Next, we examined mitochondrial ATP transport channel functionality by measuring ATP levels in mitochondria isolated from primary T cells pretreated with a NSM2-specific inhibitor ES048 ( Collenburg et al, 2017 ) which reduced NSM2 activity about 40% ( Supplementary Figure S1B ) or nocodazole. Inhibition of NSM2 as well as cytosolic tubulin elevation significantly enhanced mitochondria ATP content, indicating that both NSM2 and tubulin regulate ATP accumulation in T-cell mitochondria ( Figure 1D ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The nocodazole treatment did not affect total ATP levels in CTRL and NSM KD cells ( Figure 1C ). Next, we examined mitochondrial ATP transport channel functionality by measuring ATP levels in mitochondria isolated from primary T cells pretreated with a NSM2-specific inhibitor ES048 ( Collenburg et al, 2017 ) which reduced NSM2 activity about 40% ( Supplementary Figure S1B ) or nocodazole. Inhibition of NSM2 as well as cytosolic tubulin elevation significantly enhanced mitochondria ATP content, indicating that both NSM2 and tubulin regulate ATP accumulation in T-cell mitochondria ( Figure 1D ).…”
Section: Resultsmentioning
confidence: 99%
“…Neutral sphingomyelinase (NSM) pharmacological inhibition was achieved by incubating primary CD4 + T-cells with 1 μM GW4869 (SMPD2- and SMPD3-specific inhibitor, kindly provided by Cristoph Arenz) or with 1.5 μM ES048 ( Collenburg et al, 2017 ) 2 h before or 2 h after α-CD3/CD28 stimulation. Nucleofection of human T cells was performed according to the manufacturer’s protocol (Lonza).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A central role of PKCζ in formation of the polarity complex in epithelial cells is well documented ( 68 , 69 ). This atypical PKC also regulates chemokine-induced integrin activation and polarization in effector T cells ( 70 ), and we have recently shown that SDF-1α driven physical T cell polarization on fibronectin and inflamed endothelial cells is also NSM dependent ( 71 ). The ability of PKCζ to bind ceramide and its role in cilia formation in stem cells and neural progenitors and in polarization of primitive ectodermal cells has been previously established ( 54 , 56 , 72 , 73 ).…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, recruitment and migration of T cells regulated by ceramide/sphingomyelinases under both homeostatic and inflammtory conditions is recently noted. 8 The promotion of immune cells infiltration and chemotaxis into tumor will shed light on efficacious treatment and perpetual eradication of tumors. At this end, ceramide-driven immune cell migration would be another novel topic of immune therapies for human tumors.…”
Section: Ceramide Is a Potential Activator Of Immune Responses Againsmentioning
confidence: 99%